2008
DOI: 10.1103/physrevb.77.121301
|View full text |Cite
|
Sign up to set email alerts
|

Dressed excitons within an incoherent electron gas: Observation of a Mollow triplet and an Autler-Townes doublet

Abstract: We demonstrate that the interaction between excitons and a sea of incoherent electrons does not preclude excitons dressing by light. We investigate if exciton-electron scattering plays some inhibiting role in the coherent light-exciton coupling by measuring the dynamical absorption spectrum of a modulation-doped CdTe quantum well that shows clear evidence for significant electron scattering of the excitonic states. We show the occurrence of dressed and correlated excitons by detecting quantum coherent interfer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…For the purpose of inhibiting the hole tunneling between valence bands, we here consider that the central dot is identical to the left dot but structural asymmetry with the right dot. This structural asymmetry is similar to the case shown in the double quantum dots system 36 , 37 , 42 44 . With a gate (bias) voltage being applied along the growth direction, as shown in Fig.…”
Section: Resultssupporting
confidence: 83%
“…For the purpose of inhibiting the hole tunneling between valence bands, we here consider that the central dot is identical to the left dot but structural asymmetry with the right dot. This structural asymmetry is similar to the case shown in the double quantum dots system 36 , 37 , 42 44 . With a gate (bias) voltage being applied along the growth direction, as shown in Fig.…”
Section: Resultssupporting
confidence: 83%
“…The ultimate limitation of the spin flip time is the time scale of the nonlinear spinor polaritonpolariton interactions, which is expected to be much faster. [34][35] [36] In the tristable regime, whereas the decay of a given spin population is as fast as in the bistable case, the rise time of the majority spin population is around 300 ps. Such a long time is absolutely unexpected in purely polaritonic systems, which usually feature dynamics in the range of a few ps.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Some of these effects were partially observed in single quantum dots (QDs). For example, it has been confirmed that under strong optical excitation, the interference between the exciton-biexciton transition produces a dip in the optical absorption line.…”
Section: Introductionmentioning
confidence: 99%